Optimasi Perbandingan Monomer Fungsional dan Pengikat Silang (Crosslinker) untuk Sintesis IIPs-Zn2+ Menggunakan Metode Fotopolimerisasi - Rajab Miko; Alizar Ulianas (MASALIQ, 2026)
Environmental pollution by heavy metals, particularly Zn2+ ions, has become a serious problem due to increasing industrial activity and their potential toxic effects on ecosystems and human health, thus requiring effective and selective separation methods. This study aims to analyze the effect of variations in the amounts of methacrylic acid (MAA) as the functional monomer and ethylene glycol dimethacrylate (EGDMA) as the crosslinker on the adsorption capacity of Ion Imprinted Polymers (IIPs)-Zn synthesized using the photopolymerization method. This study employed a quantitative approach with an experimental design through variations in the composition of MAA and EGDMA, after which the adsorption capacity was tested and analyzed comparatively. The results showed that the optimum adsorption capacity was obtained with the use of 10 mmol MAA at 3.50 mg/g and 15 mmol EGDMA at 3.65 mg/g. Increasing the amounts of MAA and EGDMA beyond the optimum conditions caused a decrease in adsorption capacity due to the formation of an overly dense polymer structure and low porosity, thereby hindering the diffusion of Zn2+ ions into the active sites. These findings indicate that the balance between the amount of functional monomer and crosslinker largely determines the successful formation of selective and efficient imprinting sites. Thus, this study contributes to understanding the mechanism of IIPs formation and provides practical implications for the development of selective adsorbents for the treatment of waste containing heavy metals.